THE EFFECTIVENESS OF GIVING DATES AGAINST INCREASED HEMOGLOBIN LEVELS IN ANEMIC ADOLESCENT GIRL: SYSTEMATIC REVIEW - Ayu Andini Triana; Popi Sopiah; Rafika Rosyda (Buletin Veteriner Udayana, 2024)
The most common nutritional problem suffered by children and adolescents throughout the world is iron deficiency anemia (ADB) which occurs in developing countries, including Indonesia. One of the main causes of anemia in society is iron deficiency anemia, which occurs due to a lack of iron in the blood, which can be caused by malnutrition. Anemia can be prevented with non-pharmacological therapy, one of which is dates which can increase hemoglobin levels because they contain high levels of iron. Objective of this article was to review and synthesize the results of existing research findings regarding the effectiveness of giving dates to increase hemoglobin levels in anemic adolescent girls. This research is a systematic review by reviewing several articles from 3 databases, namely Google Scholar, PUBMED and Cochrane Library, so that 12 relevant articles were obtained for further review. The results of a research review of 12 articles stated that dates are a non-pharmacological therapy that is able to increase hemoglobin levels in adolescent girls by containing many ingredients that are good for the health of adolescent girls so that they can prevent anemia. There is an effect of giving dates on increasing hemoglobin levels in anemic adolescent girls.